Biopsy-Proven Loeffler Endocarditis Successfully Treated With Steroids. Issue 8 (24th February 2015) - Inoue, Takeshi; Watanabe, Chiaki; Ayukawa, Hiroyuki; Nadahama, Tetsuya; Hosokawa, Atsushi; Beppu, Koki; Oya, Hidefumi; Sasaki, Yoshio; Takeda, Shinichi; Shirasaka, Akihiro; Doi, Tetsuya; Hashimoto, Tetsuo; et al.
Abstract : Supplemental Digital Content is available in the text.